Characterization of serotonin‐5‐HTR1E signaling pathways and its role in cell survival. Issue 5 (20th April 2023) - Sharma, Vinay Kumar; Campbell, Kiersten; Yang, Xuyu; Dale, Ryan; Loh, Y. Peng
Abstract: 5‐Hydroxytryptamine receptor 1E (5‐HTR1E) is reported to activate cyclic AMP (cAMP) and extracellular‐signal related kinases (ERK) pathways via its ligands and binding partners, but the detailed mechanism underlying the serotonin‐induced 5‐HTR1E signaling is still not known. In the present study, we determined the cellular regulators of ERK and cAMP signaling pathways in response to serotonin‐induced 5‐HTR1E activation in 5‐HTR1E overexpressing HEK293 cells. We found that Pertussis Toxin (PTX) treatment completely reversed the effect of serotonin‐5‐HTR1E mediated signaling on cAMP and ERK pathways, confirming the involvement of a Gαi‐linked cascade. We also observed that Gβγ and Gq were not associated with 5‐HTR1E activation, while blocking protein kinase A (PKA) inhibited ERK signaling only, and had no effect on cAMP. Additionally, serotonin‐stimulated ERK1/2 phosphorylation was similar in 5‐HTR1E overexpressing, β‐arrestin‐deficient HEK293 cells and is solely dependent on G protein signaling. siRNA mediated gene knockdown studies in SH‐SY5Y cells revealed that the inhibition of 5‐HTR1E reduced the expression of cMyc, Cyclin D1, Cyclin E and BCL2 genes which are related to cell cycle regulation and survival. MTT assays showed that 5‐HTR1E knockdown in SHSY‐5Y and U118 cells inhibited cell survival significantly. In addition to the signaling mechanism, we also performed RNA‐seq analysis in 5‐HTR1E overexpressing HEK293 cells and found that 5‐HTR1E can regulate the expression of Receptor activity modifying protein 1 ( RAMP1 ), Nuclear receptor 1 ( NR4A1 ) and other Cyclin genes. These findings indicate that serotonin interaction with 5‐HTR1E receptor simultaneously activates cAMP and ERK pathway in HEK293 cells and its expression is important for cell survival. Abstract : 5‐HTR1E, a Giα linked serotonin receptor can inhibit cAMP pathway independent of PKA while increasing ERK phosphorylation via PKA/PI3‐K activation which is critical for cell survival.